Efficacy of ertapenem, gentamicin, fosfomycin, and ceftriaxone for the treatment of anogenital gonorrhoea (NABOGO): a randomised, non-inferiority trial. Issue 5 (May 2022) - de Vries, Henry J C; de Laat, Myrthe; Jongen, Vita W; Heijman, Titia; Wind, Carolien M; Boyd, Anders; de Korne-Elenbaas, Jolinda; van Dam, Alje P; Schim van der Loeff, Maarten F; ,; Bruisten, Sylvia; Hoornenborg, Elske; et al.
Summary: Background: Neisseria gonorrhoeae causes gonorrhoea, a common sexually transmitted infection. Emerging strains resistant to first-line ceftriaxone threaten N gonorrhoeae management. Hence, alternative treatments are needed. We aimed to evaluate the efficacy of ertapenem, gentamicin, and fosfomycin as alternative treatments for anogenital N gonorrhoeae . Methods: In a randomised, controlled, double-blind, non-inferiority trial (three experimental groups and one control group) at the Centre for Sexual Health in Amsterdam, Netherlands, we included adults aged 18 years or older, with anorectal or urogenital gonorrhoea. With random permuted blocks, participants were randomly assigned (1:1:1:1) to receive intramuscular 500 mg ceftriaxone (control group), intramuscular 1000 mg ertapenem, intramuscular 5 mg/kg gentamicin (maximum 400 mg), or oral 6 g fosfomycin. The primary outcome was the proportion of participants with a negative nucleic acid amplification test of the predefined primary infected site, 7−14 days after treatment. The primary analysis was per protocol (ie, excluding those lost to follow-up). The modified intention-to-treat analysis included all randomly assigned patients with anogenital gonorrhoea considering those lost-to-follow-up as treatment failure. Non-inferiority was established if the lower Hochberg-corrected 95% CI for difference between the experimental and control groups was greater than −10%. For the analysis of adverse events, we included all participants who received medication. The trial was registered at ClinicalTrials.gov (NCT03294395 ) and is complete. Findings: Between Sept 18, 2017, and June 5, 2020, from 2160 patients invited to participate, we assigned 346 (16%) participants to receive either ceftriaxone (n=103), ertapenem (n=103), gentamicin (n=102), or fosfomycin (n=38). The fosfomycin group was terminated early after interim analysis revealed less than 60% efficacy. In the primary per-protocol analysis, 93 (100%) of 93 patients in the ceftriaxone group, 86 (99%) of 87 patients in the ertapenem group, 79 (93%) of 85 patients in the gentamicin group, and four (12%) of 33 patients in the fosfomycin group cleared N gonorrhoeae (risk difference vs ceftriaxone −0·01 [95% CI −0·08 to 0·05] for ertapenem and −0·07 [−0·16 to −0·01] for gentamicin). Thus, ertapenem proved non-inferior to ceftriaxone. In mITT analysis, risk differences versus ceftriaxone were −0·08 (−0·17 to 0·003) for ertapenem and −0·11 (−0·21 to −0·04) for gentamicin. We observed a higher proportion of patients with at least one adverse event in the ertapenem group (58 [56%] of 103) and fosfomycin group (36 [95%] of 38) versus the ceftriaxone group (24 [23%] of 103). Interpretation: Single-dose 1000 mg ertapenem is non-inferior to single-dose 500 mg ceftriaxone in gonorrhoea treatment. Yet, 5 mg/kg gentamicin (maximum 400 mg) is not non-inferior to ceftriaxone. Ertapenem is a potential effective alternative for anogenital N gonorrhoeae infections and merits evaluation for ceftriaxone-resistant infections. Funding: ZonMw and GGD-Amsterdam. Translation: For the Dutch translation of the abstract see Supplementary Materials section.